Harmonic superspace from the Ad'S IND. 5' × 'S POT. 5' pure spinor formalism - Fleury, Thiago Simonetti [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The Maldacena’s conjecture or (AdS/CFT) has been one of the most studied topics in high energy physics since its formulation. One of the versions of the conjecture is the duality between the theory of type IIB superstrings in the background Ad'S IND. 5' × 'S POT. 5' supported by a Ramond-Ramond ?ux and the theory of N = 4 superYang-Mills in four dimensions. Although the action for the superstrings in this background is known both in the Green-Schwarz and in the pure spinor formalisms, an explicit super?eld construction of the vertex operators of the theory is an open problem. In this thesis, using the pure spinor formalism, we explicitly construct the vertex operators corresponding to supergravity states close to the boundary ofAdS. The conjecture predicts that every on-shell superstring state is dual to a gaugeinvariant operator of N = 4d = 4 super-Yang-Mills, in particular, the supergravity states are dual to Half-BPS operators. It is possible to describe all the Half-BPS operators and their duals as super?elds in harmonic superspace. The results for the vertex operators are described in terms of these dual super?elds in agreement with the prediction of the conjecture

A conjectura de Maldacena ou (AdS/CFT) desde a sua formulação é um dos tópicos em física de altas energias mais estudados. Uma das versões da conjectura é a dualidade entre a teoria de supercordas do tipo IIB em um background Ad'S IND. 5' × 'S POT. 5' suportado por um ?uxo Ramond-Ramond e a teoria deN = 4 super-YangMills em quatro dimensões. Embora a ação para supercordas neste background seja conhecida tanto no formalismo de Green-Schwarz como no formalismo de espinores puros, a construção explícita dos operadores de vértice da teoria em termos de supercampos é um problema em aberto. Nesta tese, os operadores de vértice do formalismo de espinores puros correspondentes aos estados de supergravidade são construídos próximos a fronteira de AdS. A conjectura prevê que todo estado na camada de massa da supercorda é dual a um operador invariante de gauge de N = 4 d = 4 super-Yang-Mills, em particular, os estados de supergravidade são duais a operadores Half-BPS. Os operadores Half-BPS e seus duais podem ser descritos como supercampos em um superespaço harmônico. Os resultados obtidos para os operadores de vértice são descritos em função desses supercampos duais de acordo com o previsto pela conjectura
Keywords: Fisica matematica; Teoria das supercordas; Supersimetria; Supergravidade